Territories of experience: performance as a formative process in the exhibition area, in the atelier and in the classroom (Revista Apotheke, 2024)
The focus of this four-handed writingis on sharing a process of artistic and pedagogical production in the context of the FaEat UFMG. Classroom, atelier and art gallery as territories of experience and formation for artists, teachers, students and the general public. In thissense, teacher, artist and students from the Pedagogy courses hare the workentitled “Com-Tato” by Thalita Amorim and participate as co-authors of the performance proposed by the work. The impacts, nuances and perceptions of these encounters are recorded through the body, the line, the image and the word, through different paths, in ordertoallowanimmersioncrossed by provocations that move between a esthesia, cognition and a reflection.
Keywords: formation; experience; performance; art; education